CONTRIBUTION OF RENEWABLE ENERGY TO CLIMATE CHANGE MITIGATION IN EU: THE CASE OF ROMANIA - PAUL CALANTER (Global Economic Observer)
For the European Union, the advancement of renewable energy is a priority primarily due to climate change mitigation measures, but also because it can be easily identified and exploited while assuring the sustainable development across EU. Under the Green Deal ambitions UE aims to gradually reduce greenhouse gas emissions, especially carbon dioxide, to limit climate change and to achieve climate neutrality by 2050. Renewable energy plays a key role in this regard. In 2022, Romania had a significant share of energy from renewable sources. Also, forecasts indicate that Romania has onshore wind capacity that could generate twice as much electricity as current consumption. The following paper aims to carry out an analysis of Romania's progress in the field of renewables. The research is based on the challenges and opportunities for the development of renewable energy while also highlighting, the particularities of Romania in terms of the adoption of renewable energy practices and emphasizing the strengths and weaknesses that Romania has in this domain. Our main finding shows that while in Romania has been significant progress in terms of renewable energy, there is still untapped capacity in the field requiring for more actions from the Romanian authorities and business environment.